Improving Student Understanding Through Demonstration Method in Learning Islamic Education - Gustina, Lola; Indria, Anita; Zulfikri, Zulfikri (STIT Ahlussunnah Bukittinggi, 2023)
This research describes improving students' prayer skills through the demonstration method, namely practicing directly with class III students at elementary school 57 Tukum II Bungo, Jambi. This research aims to find out whether the demonstration method can improve students' prayer skills. The type of research used was classroom action research with 16 class III student respondents. The research design uses several cycles, namely planning, action, observation, and reflection. Data was collected by conducting observations, interviews, tests, and documentation, which became the data source for Islamic Education teachers and class III students. Data is analyzed through student learning completeness. Research results: i) students' understanding through the demonstration method of prayer material which was carried out in class III at elementary school 80 Tukum II Bungo, Jambi showed that it was successful in improving students' prayer skills. This can be seen from the analysis of the results of prayer practice where the initial pre-cycle ability consisted of 6 students who completed it with a percentage of 37.5%. In the first cycle, there were 9 students with a percentage of 56.25%, in the second cycle there were 12 students with a percentage of 75% and in the third cycle the Islamic Education target was 16 students, a percentage of 100%. ii) inhibiting factors and supporting factors in class III students' understanding: i) inhibiting factors, namely the time factor, the student's grasping power factor, and the lack of teaching aids. ii) supporting factors, namely learning becomes clearer and reduces student misunderstandings.